2020
DOI: 10.5603/pmpi.2020.0028
|View full text |Cite
|
Sign up to set email alerts
|

Need for palliative care in patients admitted to emergency departments of three tertiary hospitals: evidence from a Latin-American city

Abstract: Background: Emergency departments (ED) serve as a contact point for critically ill patients. According to experience, a fraction of patients visiting ED present with symptoms and require palliative care; however, the prevalence of these patients has not been determined in Peru so far. Objectives: To estimate the prevalence of advanced disease in patients admitted to ED and identify among them the need for palliative care. Patients and methods: In the ED of 3 tertiary hospitals in Lima all adult patients had an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 0 publications
0
8
0
2
Order By: Relevance
“…The quality of 22 studies were assessed using the NOS (see Appendix 5) 12,16,17,18,20‐26,30‐36,38‐40,46 . The majority of these studies included a representative cohort of participants and sufficient follow‐up.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The quality of 22 studies were assessed using the NOS (see Appendix 5) 12,16,17,18,20‐26,30‐36,38‐40,46 . The majority of these studies included a representative cohort of participants and sufficient follow‐up.…”
Section: Resultsmentioning
confidence: 99%
“…43 Another study reported that the SQ had moderate to strong correlation with the Caregiver Burden Score and Risk Instrument for Screening in the Community, but a poor correlation between the Clinical Frailty scale and the EQ-5D. 44 While Tineo et al 40 did not assess the psychometric properties of their screening tool, their study reported that an unpublished pilot study found that their screening tool had acceptable internal consistency (Cronbach coefficient = 0.699).…”
Section: Reliability/validitymentioning
confidence: 99%
See 1 more Smart Citation
“…Los cuidados paliativos son una alternativa terapéutica obligatoria para mejorar la calidad de vida en los pacientes con enfermedades avanzadas, sobre todo en la etapa del final de la vida (5) . En Perú, en agosto de 2018 se promulga la ley de plan nacional de cuidados paliativos para enfermedades oncológicas y no oncológicas, sin embargo actualmente los cuidados paliativos todavía no son accesibles para todos, concentrándose en las principales ciudades y con mayor aplicación para enfermedades oncológicas; pero son pocos los estudios que evalúan calidad de vida estos pacientes (6) .…”
Section: Introductionunclassified
“…Por dificultades para acceder a una atención oportuna, muchos de los pacientes con enfermedades oncológicas son atendidos en hospitales de referencia y acuden a los servicios de emergencia con posterior hospitalización, incluso cuando ya pertenecen a programas de cuidados paliativos (6) . El objetivo del presente estudio es comparar la calidad de vida percibida por pacientes con cáncer avanzado en etapas finales de vida en un hospital de referencia, con pacientes de un programa de cuidados paliativos domiciliario.…”
Section: Introductionunclassified